PI 3‐kinase delta enhances axonal PIP3 to support axon regeneration in the adult CNS - Bart Nieuwenhuis; Amanda C Barber; Rachel S Evans; Craig S Pearson; Joachim Fuchs; Amy R MacQueen; Susan van Erp; Barbara Haenzi; Lianne A Hulshof; Andrew Osborne; Raquel Conceicao; Tasneem Z Khatib; et al. (EMBO Molecular Medicine)
Abstract Peripheral nervous system (PNS) neurons support axon regeneration into adulthood, whereas central nervous system (CNS) neurons lose regenerative ability after development. To better understand this decline whilst aiming to improve regeneration, we focused on phosphoinositide 3‐kinase (PI3K) and its product phosphatidylinositol (3,4,5)‐trisphosphate (PIP3). We demonstrate that adult PNS neurons utilise two catalytic subunits of PI3K for axon regeneration: p110α and p110δ. However, in the CNS, axonal PIP3 decreases with development at the time when axon transport declines and regenerative competence is lost. Overexpressing p110α in CNS neurons had no effect; however, expression of p110δ restored axonal PIP3 and increased regenerative axon transport. p110δ expression enhanced CNS regeneration in both rat and human neurons and in transgenic mice, functioning in the same way as the hyperactivating H1047R mutation of p110α. Furthermore, viral delivery of p110δ promoted robust regeneration after optic nerve injury. These findings establish a deficit of axonal PIP3 as a key reason for intrinsic regeneration failure and demonstrate that native p110δ facilitates axon regeneration by functioning in a hyperactive fashion.